A Splenic Marginal Zone Lymphoma Case Presenting with Cyanosis, Spider Angiomas, and Polycythemia - Esma Güldal Altunoğlu; Muhlis Cem Ar; Nükhet Tüzüner; Kaya Sarıbeyoğlu (İstanbul Medical Journal, 2015)

(untitled)
Splenic marginal zone lymphoma (SMZL) is an indolent cancer classified among low-grade B-cell lymphomas in the World Health Organization (WHO) classification. The major characteristics of SMZL are splenomegaly, villous cytoplasmic protrusions of the lymphocytes in peripheral blood, anemia, and/or thrombocytopenia. The involvement of various organs, particularly the bone marrow or liver, can be frequently observed. SMZL has been reported to be associated with hepatitis C infection. The course of the disease is generally indolent, but aggressive behavior may be observed in a minority of patients. Here, we report a 43-year-old male hepatitis B virus carrier who presented with abdominal distension, multiple spider angiomas on the skin, and central cyanosis, leading to a diagnosis of SMZL.